Meningkatkan Aktivitas dan Prestasi Belajar Lingkaran Siswa Melalui Penerapan Teori Belajar Bruner - Indrawati Indrawati; Samsuriadi Samsuriadi (Fakultas MIPA Universitas Nahdlatul Wathan Mataram, 2021)
This study aims to improve student learning activities and achievement by applying Bruner's learning theory to the circle material. This type of research is classroom action research which is carried out in two cycles. Each cycle consists of stages of planning, implementing actions, observing, evaluating, and reflecting. The subjects of this study were students of class VIII-3 semester II of SMP Negeri 1 Batukliang, totaling 22 people. Based on the results of the evaluation of cycle I and cycle II, the average score of student learning activities was 4.4; 4.45; which has the category of activity, and very active. The average ability of teachers to manage to learn for each meeting is 4.08 in categories; 4.17; 4.64; and 4.75 in the very high category. While the average score of student evaluation results, in the first and second cycles, were 69.55 and 91.14, respectively. In addition, the calculation of the N-Gain of student learning is categorized as high with an n-gain value of 0.71. In addition, individual and classical completeness has been achieved. Thus, the application of Bruner's learning theory can increase student activity and achievement in class VIII-3 semester II of SMP Negeri 1 Batuliang on the circle material